Dystopia - Booker, M. Keith (Ipswich, Mass. : Salem Press, 2013)
To be dystopian, a work needs to foreground the oppressive society in which it is set, using that setting as an opportunity to comment in a critical way on some other society, typically that of the author and/or the audience. In other worlds, the bleak dystopian world should encourage the reader or viewer to think critically about it, then to transfer this critical thinking to his or her own world. This volume in the Critical Insights series presents a variety of new essays on the perennial theme. --from publisher description
On dystopia / M. Keith Booker -- Critical contexts : Critical reception / Derek Thiess ; Ursula K. Le Guin's critical dystopias / Raffaella Baccolini ; Totalitarian technocracies / Thomas Horan ; Compare/contrast: media culture, conformism, and commodification in Ray Bradbury's Fahrenheit 451 and M. T. Anderson's Feed / M. Keith Booker -- Critical readings : Science, politics, and utopia in George Orwell's Nineteen eighty-four / Tony Burns ; Need it all end in tears? The problem of ending in four classic dystopias / Andrew Milner ; "They got me a long time ago": the sympathetic villain in Nineteen eighty-four, Brave new world, and Fahrenheit 451 / Rafeeq O. McGiveron ; "The wretched refuse of your teeming shore": overpopulation and social breakdown in Harry Harrison's Make room! Make room! / Brian Ireland ; Rationalism, revolution, and utopia in Yevgeny Zamyatin's We / Peter G. Stillman ; The meaning of "I" in Ayn Rand's Anthem / Aaron Weinacht ; Frontierism and dystopian representations of home in F. Pohl and C. M. Kornbluth's The space merchants / Enrica Picarelli ; A Nineteen eighty-four for the twenty-first century: John Twelve Hawks's Fourth realm trilogy as critical dystopia / Alexander Charles Oliver Hall ; r
Includes bibliographical references (p. 279-281) and index.
Keywords: Dystopias in literature; Utopias in literature; Fiction -- 20th century -- History and criticism; Fiction -- 21st century -- History and criticism; Science fiction -- History and criticism; Science fiction films -- History and criticism; Literature and society